2010
DOI: 10.1186/1471-2407-10-256
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic features of tumor infiltrating lymphocytes from mammary carcinomas in female dogs associated with prognostic factors and survival rates

Abstract: BackgroundThe immune system plays an important role in the multifactorial biologic system during the development of neoplasias. However, the involvement of the inflammatory response in the promotion/control of malignant cells is still controversial, and the cell subsets and the mechanisms involved are poorly investigated. The goal of this study was to characterize the clinical-pathological status and the immunophenotyping profile of tumor infiltrating lymphocytes and their association with the animal survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
5
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 40 publications
(58 reference statements)
6
70
5
14
Order By: Relevance
“…Diversos autores consideram o tamanho tumoral e o estadiamento clínico os parâmetros prognósticos mais importantes (Peleteiro, 1994;Misdorp et al 1999;Cavalcanti & Cassali, 2006;Estrela-Lima et al, 2010;Cassali et al, 2011). Tumores menores que três centíme-tros sem invasão linfática apresentam melhor prognósti-co, quando comparados com aqueles maiores ou que já apresentam metástase para linfonodos (Queiroga & Lopes, 2002;Ferreira et al, 2009).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Diversos autores consideram o tamanho tumoral e o estadiamento clínico os parâmetros prognósticos mais importantes (Peleteiro, 1994;Misdorp et al 1999;Cavalcanti & Cassali, 2006;Estrela-Lima et al, 2010;Cassali et al, 2011). Tumores menores que três centíme-tros sem invasão linfática apresentam melhor prognósti-co, quando comparados com aqueles maiores ou que já apresentam metástase para linfonodos (Queiroga & Lopes, 2002;Ferreira et al, 2009).…”
Section: Resultsunclassified
“…A maioria dos tumores apresentava integridade cutânea; entretanto cabe ressaltar que, neste estudo, 100% (33/132) dos tumores que apresentavam ulcerações eram malignos. Sabe-se que os tumores de crescimento rápido, aderentes, com grandes áre-as de necrose, ulcerados ou com acometimento de planos cutâneos adjacentes estão associados a pior prognóstico e menor tempo de sobrevida (Peleteiro, 1994;Cassali, 2002;Estrela-Lima, 2010).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…The role of leukocytes in the tumor microenvironment is not yet fully understood, and several efforts have been made to understand the role of these cells in tumor development. Studies have shown that the lymphocytes presence in mammary mixed tumor (MMT) may be involved in a better or worse prognosis for the patient [1,10].…”
Section: Introductionmentioning
confidence: 99%